Social networks : promoting Mexican popular cultures and building a participatory culture - Montes Vega, Diana (2012)
For over 30 years, the General Direction of Popular Cultures has been in charge of promoting, preserving, and disseminating the cultural diversity of Mexico, regarding indigenous and popular cultural practices. With the increasing popularization of Social Networks, it has become almost indispensable to join Social Networks in order to exist digitally, weather you are an individual, an institution or government. Taking this fact in consideration, in 2011 the Direction of Popular Cultures joined the most utilized social Networks in México: Twitter, Facebook and YouTube, as a way to keep users updated about the activities and general information generated by the Direction. Departing form the point of view that considers Internet as a democratic space where everyone has an equal right to be represented in, this thesis explores the use that the governmental institution has given to Social Networks, and how they interact with their users to get fulfilled the institutional goals of disseminate the knowledge about indigenous cultures while trying to create a participatory culture.